Protein-rich diet decreases survival, but does not alter reproduction, in fertile ant workers - Choppin, Marina; Schall, Miriam; Feldmeyer, Barbara; Foitzik, Susanne (Frontiers in Ecology and Evolution, 2023)
Aging is associated with diverse molecular processes such as oxidative damage, decrease in immunocompetence, or increase in epigenetic abnormalities, mutations, and inflammations. Many of these processes are linked to nutrient-sensing signalling pathways, suggesting that diet plays a critical role in the aging process. In fact, the protein content in the diet can affect both longevity and fecundity, but often in opposite directions. In many solitary organisms, protein-rich diets dramatically shorten lifespan, but increase egg production. We used the ant Temnothorax rugatulus to investigate the effect of the protein to carbohydrate ratio in the diet on the survival and fecundity of fertile workers. We fed colonies either a moderately high-carbohydrate or high-protein diet (1:2 and 2:1 respectively) and monitored worker survival and egg production over nine weeks. The protein-rich diet did not alter the ability of workers to lay eggs, but reduced worker survival, suggesting that consuming large amounts of protein may shorten lifespan in fertile ant workers without promoting reproduction. Our study shows for the first time that a protein-rich diet reduces the overall fitness of fertile workers.